Polymer blends of poly(ethylene-2,6-naphthalate) with polystyrene compatibilized by styrene-glycidyl methacrylate copolymers. I. Rheology, morphology, and mechanical properties - Huang, JM; Ju, MY; Hung, CJ; Luoh, WC; Chang, FC (My University, 2003)
The compatibilization of blends of poly(ethylene-2,6-naphthalate) (PEN) with polystyrene (PS), through the styrene-glycidyl methacrylate copolymers (SG) containing various glycidyl methacrylate (GMA) contents, was investigated in this study. SG copolymers are able to react with PEN terminal groups during melt blending, resulting in the formation of desirable SG-g-PEN copolymers in the blend. These in situ formed copolymers tend to reside along the interface preferentially as the result of interfacial reaction and thus function as effective compatibilizers in PEN/PS blends. The compatibilized blends exhibit higher viscosity, finer phase domain, and improved mechanical properties. It is found that the degree of grafting of the in situ formed SG-g-PEN copolymer has to be considered as well. In blends compatibilized with the SG copolymer containing higher GMA content, heavily grafted copolymers would be produced. The length of the styrene segment in these heavily grafted copolymers would be too short to penetrate deep enough into the PS phase to form effective entanglements, resulting in the lower compatibilization efficiency in PEN/PS blends. Consequently, the in situ formation of SGg-PEN copolymers with an optimal degree of grafting is the key to achieving the best performance for the eventually produced PEN/PS blends through SG copolymers. (C) 2002 Wiley Periodicals, Inc. J Appl Polym Sci 87: 967-975, 2003.
Keywords: PEN; PS; styrene-glycidyl methacrylate copolymer; reactive compatibilization; graft copolymer